2021
DOI: 10.1111/jog.14671
|View full text |Cite
|
Sign up to set email alerts
|

Morphological changes in the experimental model of polycystic ovary syndrome and effects of vitamin D treatment

Abstract: Aim This research was designed to develop an animal model by inducing polycystic ovary syndrome (PCOS) with dehydroepiandrosterone (DHEA) and observe reproductive and morphological changes after treatment with vitamin D. Materials and Methods Thirty pre‐pubertal female Sprague–Dawley (SD) dams were recruited. The animals were distributed 10 each in control, PCOS and vitamin D‐treated groups. In control group 0.2 ml of sesame oil was given. PCOS group was administered DHEA by the daily dose of 6 mg/kg for 30 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Moreover, vitamin D stimulates the expression of mitochondrial transcription factor A, increases mtDNA copy number, and improves the integrity of the mitochondrial membrane ( 98 ). In DHEA-induced PCOS rat models, vitamin D supplementation improved ovarian and uterine morphology, and reduced body weight and obesity ( 99 ). Additionally, vitamin D regulates steroid production and reduces progesterone (P) and E 2 production by reducing the expression of steroidogenic enzymes.…”
Section: Treatment Strategy Of Pcosmentioning
confidence: 99%
“…Moreover, vitamin D stimulates the expression of mitochondrial transcription factor A, increases mtDNA copy number, and improves the integrity of the mitochondrial membrane ( 98 ). In DHEA-induced PCOS rat models, vitamin D supplementation improved ovarian and uterine morphology, and reduced body weight and obesity ( 99 ). Additionally, vitamin D regulates steroid production and reduces progesterone (P) and E 2 production by reducing the expression of steroidogenic enzymes.…”
Section: Treatment Strategy Of Pcosmentioning
confidence: 99%
“…Vitamin D treatment stimulates the expression of the TFAM (mitochondrial transcription factor A) gene, the main nuclear regulator of mitochondria biogenesis, leading to a higher copy number of mtDNA and improved membrane integrity [107]. Vitamin D supplementation improved ovary and uterus morphology and decreased weight and obesity levels in DHEA-induced PCOS rat models [108]. Additionally, vitamin D regulates steroidogenesis by reducing the expression of steroidogenic enzymes and reduces the production of progesterone and 17B-estradiol [109].…”
Section: Mitochondria-targeted Therapymentioning
confidence: 99%
“…In current work, we observed that letrozole-treated rats exhibited a significant increase in body weight and a decrease in serum 25(OH)D concentration; these results are consistent with previous observations ( Grzesiak et al, 2021 ). Moreover, a previous study confirmed amelioration of weight gain after a subcutaneous injection of 1,25(OH) 2 D 3 ( Azhar et al, 2021 ). Furthermore, the results of randomized, placebo-controlled clinical trials conducted in women with PCOS found that vitamin D supplementation led to metabolic benefits ( Foroozanfard et al, 2017 ; Javed et al, 2019 ).…”
Section: Discussionmentioning
confidence: 60%